Religious Spaces in the Far East: Women's Travel and Writing in Manila and Macao - Owens, Sarah E. (Challenging Women's Agency and Activism in Early Modernity, 2021)
This essay examines the travel and writings of Sor Magdalena de Cristo (1575–1653), one of the co-founders of the first Franciscan convent in the Philippines and another convent in Macao, China. Her harrowing journey emerges in a letter written by her confessor, who was also her advocate. While in Manila, Sor Magdalena wrote her magnum opus, Floresta Fran-ciscana, a three-volume mystical treatise glorifying the Franciscan order. Based on unpublished letters and manuscripts gathered from archives in Spain and Italy, this essay explores Sor Magdalena’s role as an intrepid traveler and author, and also analyzes how she collaborated and formed a writing community with her peers, helping her Spanish sisters cultivate their own religious and literary space in the Far East.